Association between high dietary intake of the n−3 polyunsaturated fatty acid docosahexaenoic acid and reduced risk of Crohn's disease. Issue 8 (24th February 2014) - Chan, S. S. M.; Luben, R.; Olsen, A.; Tjonneland, A.; Kaaks, R.; Lindgren, S.; Grip, O.; Bergmann, M. M.; Boeing, H.; Hallmans, G.; Karling, P.; Overvad, K.; et al.
Summary Background There are plausible mechanisms for how dietary docosahexaenoic acid (DHA), an n−3 polyunsaturated fatty acid, could prevent Crohn's disease (CD). Aim To conduct a prospective study to investigate the association between increased intake of DHA and risk of CD. Methods Overall, 229 702 participants were recruited from nine European centres between 1991 and 1998. At recruitment, dietary intakes of DHA and fatty acids were measured using validated food frequency questionnaires. The cohort was monitored through to June 2004 to identify participants who developed incident CD. In a nested case–control analysis, each case was matched with four controls; odds ratios (ORs) were calculated for quintiles of DHA intake, adjusted for total energy intake, smoking, other dietary fatty acids, dietary vitamin D and body mass index. Results Seventy‐three participants developed incident CD. All higher quintiles of DHA intake were inversely associated with development of CD; the highest quintile had the greatest effect size (OR = 0.07; 95% CI = 0.02–0.81). The OR trend across quintiles of DHA was 0.54 (95% CI = 0.30–0.99, Ptrend = 0.04). Including BMI in the multivariate analysis, due to its correlation with dietary fat showed similar associations. There were no associations with the other dietary fatty acids studied. Conclusion There were inverse associations, with a biological gradient between increasing dietary docosahexaenoic acid intakes and incident Crohn's disease. Further studies in other populations should measure docosahexaenoic acid to determine if the association is consistent and the hypothesis tested in randomised controlled trials of purely docosahexaenoic acid supplementation.